Diagnosis and correction of soil nutrient problems of common beans (Phaseolus vulgaris) in the Usambara mountains of Tanzania - Smithson, James Brady; Edje, O.T.; Giller, Kenneth E. (Cambridge University Press, 1993)
Stages in the diagnosis of an interveinal leaf chlorosis in bean in the Usambara Mountains of northern Tanzania are described. Leaf tissue analysis, soil analysis, a 25 factorial trial with treatments of nitrogen, phosphorus, potassium, the trace elements copper and zinc and lime at one location and data from a series of 43 factorial trials of N, P and K demonstrated the leaf condition to be due to potassium deficiency. Large growth and yield responses to N, P and K were recorded. The responses were accompanied by greater numbers of pods and seeds/pod. The application of N and K increased leaf concentrations of the respective elements but depressed the concentrations of other major and minor elements in leaves. There were no effects of trace elements or lime.